1997
DOI: 10.1111/j.1600-0765.1997.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basic fibroblast growth factor on human periodontal ligament cells

Abstract: In order to clarify the regulatory mechanisms of periodontal regeneration by basic fibroblast growth factor (bFGF), effects of bFGF on proliferation, alkaline phosphatase activity, calcified nodule formation and extracellular matrix synthesis of human periodontal ligament (PDL) cells were examined in this study. bFGF enhanced the proliferative responses of PDL cells in a dose-dependent manner. The maximum mitogenic effect of bFGF on PDL cells was observed at the concentration of 10 ng/ml. In contrast, bFGF inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
142
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 52 publications
20
142
1
2
Order By: Relevance
“…The stimulation of ACL cell proliferation by FGF-2 is consistent with previous reports [6,29,41]. The combination of cell proliferation and slowing of scaffold dimensional change may be useful for applications where it is desirable for the scaffold to maintain its shape during remodeling.…”
Section: Discussionsupporting
confidence: 78%
“…The stimulation of ACL cell proliferation by FGF-2 is consistent with previous reports [6,29,41]. The combination of cell proliferation and slowing of scaffold dimensional change may be useful for applications where it is desirable for the scaffold to maintain its shape during remodeling.…”
Section: Discussionsupporting
confidence: 78%
“…Murakami et al observed that downgrowth of junctional epithelium was limited by bFGF-2 application when compared with sham operation in class II furcation defects 14) . In general, bFGF-2 has been reported to induce the proliferation of not only periodontal ligament cells but also gingival epithelial cells in a dose-dependent manner in vitro 8,32) . However, Takayama et al reported that co-stimulation with fetal calf serum inhibited bFGF2-induced-proliferation of gingival epithelial cells, but synergistically enhanced bFGF-2-induced periodontal ligament cell proliferation 32) .…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to determine the optimal dose of bFGF-2 for periodontal regeneration in dogs from several previous reports. bFGF-2 had a dose-dependent effect on periodontal regeneration at a dose ranging from 0 to 0.16% per implant [3][4][5][6][7][8][9][10][11][12][13][14][15][26][27][28][29] . Hayashi et al reported that new bone formation was smaller in the 0.56% bFGF-2 (100 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant compared to the 0.056% bFGF-2 (10 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant; however, there were no significant differences between them 29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiogenic and fibroblast stimulatory properties of FGF-2 during wound healing and its chemotactic and proliferative effects on PDL cells [90,91] suggest its use for periodontal regenerative therapeutic approaches. In preclinical studies, this growth factor was evaluated for the treatment of different types of periodontal bone defects, in dogs [92][93][94][95] and non-human primates [96].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%